2018
DOI: 10.20517/2394-5079.2018.17
|View full text |Cite
|
Sign up to set email alerts
|

A potential clinical based score in hepatitis C virus cirrhotic patients to exclude small hepatocellular carcinoma

Abstract: Aim: Hepatitis C virus (HCV) cirrhosis is an important cause of hepatocellular carcinoma (HCC). This study aimed to identify factors of HCC presence among HCV cirrhotic patients with and without small diameter HCC (≤ 3 cm). Methods: A case control transversal study between 1998 and 2003 including 93 patients: 31 with small diameter HCC and 62 without HCC. Groups were matched by age and gender. Multiple logistic regression analysis using Akaike Information Criteria to estimate the probability of HCC was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…These results are in accordance with Ren et al 27 who find a significant difference between HCC and cirrhotic patients in albumin, INR, and AFP. Paranaguá et al and Mohamed et al also find a significant difference between HCC and cirrhotic HCV patients in AST, ALT, and AFP 33,34 . Mohamed et al 35 had similar results, they found a significant difference in HCC patients in AST, ALT, and T bilirubin, INR, serum AFP, serum creatinine and platelet.…”
Section: Discussionmentioning
confidence: 77%
“…These results are in accordance with Ren et al 27 who find a significant difference between HCC and cirrhotic patients in albumin, INR, and AFP. Paranaguá et al and Mohamed et al also find a significant difference between HCC and cirrhotic HCV patients in AST, ALT, and AFP 33,34 . Mohamed et al 35 had similar results, they found a significant difference in HCC patients in AST, ALT, and T bilirubin, INR, serum AFP, serum creatinine and platelet.…”
Section: Discussionmentioning
confidence: 77%
“…[32] The present study came upon a correlation of total bilirubin values and MELD score, markers of liver function with HCC occurrence, as previously reported. [33] In addition to the risk for developing HCC over time, some of these parameters (such as bilirubin levels, AFP, platelet count and MELD score) may be associated with the presence of HCC at the time of assessing patients with cirrhosis due to hepatitis C. [34] Although some evidence of association between tobacco consumption and HCC is recognized, [35][36][37][38] we could not demonstrate this correspondence in our population. In order to avoid bias, the study recruitment policy excluded patients with signi cant and current alcohol intake, also an important risk factor for HCC emergence.…”
Section: Discussionmentioning
confidence: 84%